Comparative Analysis of Tensile Properties of Hydraulic Asphalt Concrete - ZHANG Yang (Renmin Zhujiang)
In order to explore the quantitative difference of the test methods on the tensile properties of hydraulic asphalt concrete,this paper prepares samples with different gradation indexes according to the aggregate gradation theory,measures the tensile properties through uniaxial tensile test,splitting test and trabecular bending test,analyzes the indexes such as strength,deformation and critical strain energy density,identifies the changing law of tensile properties of asphalt concrete,and specifies the difference of the three test results.The test results shows that:The stress-strain curve of asphalt concrete shows strain softening when it is subjected to uniaxial tensile,and hyperbolic liner when it is subjected to splitting stress,and the strain softening is affected by the gradation index when it is subjected to bending stress.Compared with the uniaxial tensile test results,the difference in the deformation modulus measured by the splitting test is smaller,the strength and peak strain are 10% higher,and the critical strain energy density is 20% higher;the trabecular bending test results are 1.3~2.8 times that of uniaxial tensile test.The uniaxial tensile test is preferred to determine the tensile properties of asphalt concrete.When it is not available,the splitting test can be used to measure the tensile strength and deformation modulus.